Enhancing self-resources in patients with chronic diseases: development and initial validation of the Disease and Care Management Score: Disease & Care Management Score (D&CM) - Pennini, Annalisa; Magon, Arianna; Colangelo, Antonio; Ferraro, Bruno; Caruso, Rosario (Acta Biomedica Atenei Parmensis, 2020)
Introduction: Despite the importance of the assessment in the primary care of the self-resources among patients with chronic diseases, there is not available a measurement that allows this kind of comprehensive assessment. For this reason, the aim of this study was to develop a multi-dimensional score to determine the level of self-resources in chronic patients, describing its initial validation through face and content validity. The developed score was labelled as Disease and Care Management Score. Methods: We performed a methodological study, encompassing two main phases. The first phase was aimed to develop the Disease and Care Management score, choosing the most suitable measurement to assess each pre-identified determinant of wellbeing in chronic patients. The second phase was aimed to determine the Disease and Care Management score face and content validity through the views of 20 experts. Results: Disease and Care Management score shows evidence of face and content validity. All the obtained quantitative content validity indices (i.e. Content Validity Ratio, Content Validity Indices) were higher than 0,70, showing the pertinence and the adequacy of each pre-identified measure to compute Disease and Care Management score. Conclusion: Disease and Care Management score has the potential of addressing the health coaching interventions in primary care for chronic patients. Future research should show its predictive performance, as well as the cut-off to discriminate patients.